Tâches de médiation comme outils d’enseignement/apprentissage actionnel des langues étrangères - Janowska, Iwona (Neofilolog, 2023)
Clarified and detailed in the CEFR – Companion volume (2020), mediation gains a new dimension. The proposed scales of mediation activities clearly focus on action-oriented, situational use of language. However, the theoretical description of these activities, the scaling of specific skills are not enough to be able to effectively develop mediation competence in pedagogical practice. In order to understand the specifics of mediation activities, concrete guidelines are needed for the construction mediation tasks and application in the process of language teaching and learning. The purpose of this article is to present selected issues related to the creation and implementation of mediation tasks, which give new meaning to the learning process and can be seen as a practical form of applying an action-oriented approach.